The Existence of Traditional Markets After Revitalization in Semarang Municipality - Kistanti, Nurjannah Rahayu; Karsinah, Karsinah (Efficient: Indonesian Journal of Development Economics, 2020)
This study aims at identifying the existing condition of traditional markets after revitalization in Semarang Municipality, analyzing the government policies and analyzing social capital as an effort of maintaining the existence of traditional markets. This research was conducted in 2018, and the data were collected using the FGD and questionnaire. The data is analyzed using the mix method. The market existence indicators have 3 criteria, namely analysis of traditional market existence, analysis of government policies related to traditional markets, and analysis of social capital. The research results indicate that Sampangan, Rasamala and Peterongan Markets have stagnant existence direction. This means the existence of these markets is stable with neither acceleration nor declaration. Meanwhile, Bulu Market is inclined towards a declining trend. The market facility and infrastructure indicator shows that while the infrastructure is better and more modern, the number of buyers decreases and, hence, sellers income decreases. The human resources of the market administrator factor need to be improved by providing them training on healthy market management. Finally, social capital constitutes the key to the traditional market to survive in which such a matter is not found in the modern market. Penelitian ini bertujuan untuk mengidentifikasi kondisi pasar tradisional pasca revitalisasi di Kota Semarang, menganalisis kebijakan pemerintah dan menganalisis modal sosial sebagai upaya mempertahankan eksistensi pasar tradisional. Penelitian ini dilaksanakan pada tahun 2018, dan pengumpulan data dilakukan dengan menggunakan FGD dan kuesioner. Data dianalisis menggunakan mix method. Indikator keberadaan pasar mempunyai 3 kriteria, yaitu analisis keberadaan pasar tradisional, analisis kebijakan pemerintah terkait pasar tradisional, dan analisis modal sosial. Hasil penelitian menunjukkan bahwa Pasar Sampangan, Rasamala dan Peterongan memiliki arah keberadaan yang stagnan. Artinya, keberadaan pasar-pasar ini stabil tanpa adanya percepatan maupun deklarasi. Sementara itu, Pasar Bulu cenderung mengalami tren penurunan. Indikator sarana dan prasarana pasar menunjukkan bahwa meskipun sarana prasarana lebih baik dan lebih modern, jumlah pembeli menurun sehingga pendapatan penjual menurun. Peningkatan SDM pengelola pasar perlu dilakukan dengan memberikan pelatihan tentang pengelolaan pasar yang sehat. Terakhir, modal sosial merupakan kunci bertahannya pasar tradisional yang tidak terdapat dalam pasar modern.